Penelopegate : fake news et retravail d’ethos en ligne lors de la campagne présidentielle de 2017 - Baider, Fabienne H.; Constantinou, Maria (Studia Romanica Posnaniensia, 2017)
The French politician François Fillon, for a long time considered the frontrunner in the French presidential campaign, saw his strong position crumble to the third in most of the polls, after the circulation of rumors against him and his family also known as Penelopegate. Such rumors were at the heart of the 2017 French and American presidential campaigns. In fact, the terms post truth, fake news and alternative facts could be seen as symbols of the current information crisis, i.e. the mistrust felt by many readers regarding the media. The present study sets out to investigate the argumentation used to deconstruct and reconstruct François Fillon’s ethos after dissemination of such rumors on social media. Drawing on the theoretical framework developed by Amossy (2014 et al.) and Maingueneau (2004 et al.) on the analysis of self-presentation and in particular on the concepts of (re)branding and scenography, we analyze the discursive strategies deployed by discussants in face management of the French politician’s image. Our data include two different genres (tweets and posts on newspaper forums) and our findings corroborate Amossy’s research (2014) on strategies used in such face work management as denial of responsibility (sympathy), victimization (empathy) or face threats against the opponents (anger). We have also observed the use of a catastrophic scenario (fear), which was not present in Amossy’s data.